1981
DOI: 10.1093/geronj/36.6.750
|View full text |Cite
|
Sign up to set email alerts
|

Perceived and Objective Conditions As Predictors of the Life Satisfaction of Urban and Non Urban Elderly

Abstract: The effects of objective and subjective conditions on the life satisfaction of urban and non urban elderly are examined in a sample consisting of 1405 randomly selected elderly Vermonters in a four-county area of Northwestern Vermont. Results confirm that there are few significant objective differences between urban and non urban elderly. However, the non urban feel subjectively that they are better off on most conditions. Perceived evaluations of status are found to be better predictors of life satisfaction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…Because there are also so many people in urban areas, the sense of personal and private space is limited (Kivett, 1988). Furthermore, rural older adults believe they are doing well in spite of social and economic disadvantages, whereas urban older adults tend to view deficits in income, health, and social support in a more negative way, resulting in worse psychological outcomes than those of their rural counterparts (Fengler & Jensen, 1981). Kivett (1988) discussed the rural-urban paradox of actual (objective) versus perceived (subjective) life conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Because there are also so many people in urban areas, the sense of personal and private space is limited (Kivett, 1988). Furthermore, rural older adults believe they are doing well in spite of social and economic disadvantages, whereas urban older adults tend to view deficits in income, health, and social support in a more negative way, resulting in worse psychological outcomes than those of their rural counterparts (Fengler & Jensen, 1981). Kivett (1988) discussed the rural-urban paradox of actual (objective) versus perceived (subjective) life conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study the TMIG Competence Index score was significantly correlated with two items on the PGC Morale Scale: a place in the world for self and acceptance of what cannot be changed. Some studies have suggested that the difference in PGC Moral Scale between the urban and nonurban elderly may be the Yamashita/Iijima/Kobayashi result of actual or perceived differences in community and family support [16][17][18]. Identifying the predictors of a better performance in the aged may help to develop interventions to promote more successful aging [19].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have concluded that urban environment would be more favorable to life satisfaction of elderly people (Flenger and Jensen 1981), but others strongly endorse that the rural environment seems to be a better predictor of happiness (Kozma and Stones 1983). They also confirmed the importance of resources such as healthcare, social and physical activities, and community support (Kozma and Stones 1983) and the differences given between the two environments (Flenger and Jensen 1981).…”
Section: Introductionmentioning
confidence: 98%
“…Few of the factors described above have been discussed in the literature so far, especially well-being and happiness during retirement and possible differences among people living in urban and rural areas. However, first studies that compared welfare both in rural or urban areas are dated to the 1980s when Kozma and Stones (1983) and Flenger and Jensen (1981) investigated differences in happiness and life satisfaction between urban and non-urban population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation